P818 Prevalence of HPV in teenage heterosexual males after the introduction of the gender-neutral vaccination program in australia. (14th July 2019) - Chow, Eric; Tabrizi, Sepehr; Fairley, Christopher; Wigan, Rebecca; Regan, David; Hocking, Jane; Garland, Suzanne; Brotherton, Julia; Bradshaw, Catriona; Cornall, Alyssa; McNulty, Anna; Atchison, Steph; et al.
Abstract : Background: Australia introduced a school-based human papillomavirus (HPV) vaccination program for females aged 12–13 years in 2007, with a three-year catch-up to age 26; and for boys aged 12–13 from 2013, with a two-year catch-up to age 15. This study aimed to compare the prevalence of penile HPV between teenage heterosexual males in cohorts eligible or non-eligible for the school-based male vaccination program. Methods: Between 2014 and 2017, sexually active heterosexual males aged 17–19 were recruited from sexual health centres and community sources across Australia. Males provided a self-collected penile swab for HPV genotypes (Roche Linear Array) and completed a questionnaire. HPV prevalence was compared between males in two periods: 2014–2015 (non-eligible for school-based male vaccination) and 2016–2017 (eligible for school-based male vaccination). Self-reported vaccine doses were confirmed with doses reported to the National HPV Vaccination Program Register. Results: Overall, 152 males were recruited in 2014–2015 and 146 in 2016–2017. Numbers of female sex partners and condom use did not differ between the two periods. Prevalence of quadrivalent vaccine-preventable [4vHPV] genotype (6, 11, 16, 18) was low in both periods (2.6% in 2014–2015 versus 0.7% in 2016–2017; p =0.37). Compared with males recruited in 2014–2015, males in 2016–2017 had a lower prevalence of: any 37 HPV genotype (21.7% versus 11.6%; p =0.02); and any 13 high-risk genotype (15.8% versus 7.5%; p =0.03). Prevalence of low-risk HPV genotypes did not differ between the two periods ( p = 0.25). Of the males recruited in 2016–2017, 55% had received ≥1 vaccine dose. Conclusion: Prevalence of 4vHPV genotypes among teenage heterosexual males in both cohorts was low, presumably due to herd protection from the female-only vaccination program. The addition of the school-based male vaccination was associated with a lower prevalence of high-risk HPV genotypes other than genotypes 16/18. Disclosure: No significant relationships.